Which Recommendations Are You Using? A Survey of Emergency Physician Management of Paroxysmal Atrial Fibrillation - Ryan C. Daniel, BSc; Clare L. Atzema, MD, MSc; Dennis D. Cho, MD, MSc; Philip J. Davis, MD, MSc; Lorne L. Costello, MD, MSc (CJC Open, 2022)
Background: Both the Canadian Cardiovascular Society (CCS) and the Canadian Association of Emergency Physicians (CAEP) have published documents to guide atrial fibrillation (AF) management. In 2021, the CAEP updated its AF checklist. Prior to this update, the recommendations of the 2 organizations differed in several key areas, including the suggested cardioversion timeframe, the factors determining cardioversion eligibility, and anticoagulant initiation after cardioversion. Whether emergency physicians (EPs) are aware of, or adhering to, one, both, or neither of these documents is unknown. Methods: We assessed document awareness, adherence, and EP practice using a piloted questionnaire administered to EPs at 5 emergency departments in 3 provinces. Results: Of 166 survey recipients, 123 (74.1%) responded. The majority (64.7%) worked at an academic site, 38.8% identified as female, and median years in practice was 10.0. Most (93.1%) were aware of at least one of the documents; 45.7% were aware of both. Reported awareness was higher for the CCS (77.6%) vs the CAEP (61.2%) guidelines. Respondents varied in their adherence, with 40.5% using parts of both documents. Considerable practice variability occurred when recommendations conflicted. Despite its use not being recommended by either organization, half of respondents (50.0%) reported using the CHA2DS2-VASc score as their stroke-risk assessment tool. Conclusions: Although most surveyed EPs were aware of at least one organization’s AF documents, many reported using parts of both. When recommendations conflicted, EPs were divided in their decision-making. These findings emphasize the need to improve consensus between organizations and further improve knowledge translation. Résumé: Introduction: La Société canadienne de cardiologie (SCC) et l’Association canadienne des médecins d’urgence (ACMU) ont publié des documents pour orienter la prise en charge de la fibrillation auriculaire (FA). En 2021, l’ACMU a actualisé sa liste de vérification sur la FA. Avant cette actualisation, les recommandations des deux organismes différaient sur plusieurs points importants, notamment le laps de temps suggéré avant la cardioversion, les facteurs qui déterminent l’admissibilité à la cardioversion, et l’amorce du traitement anticoagulant après la cardioversion. On ignore si les médecins d’urgence (MU) connaissent ou adhère à un, à deux ou à aucun de ces documents. Méthodes: Nous avons évalué la connaissance qu’ont les MU de ces documents, leur adhésion et leur pratique grâce à un questionnaire pilote soumis aux MU de cinq services des urgences de trois provinces. Résultats: Parmi les 166 participants à l’enquête, 123 (74,1 %) y ont répondu. La majorité (64,7 %) travaillait dans un établissement universitaire, 38,8 % étaient des femmes, et le nombre médian d’années de pratique était de 10,0. La plupart (93,1 %) connaissaient au moins un des documents; 45,7 % connaissaient les deux. La connaissance rapportée était plus élevée pour les lignes directrices de la SCC (77,6 %) que pour les lignes directrices de l’ACMU (61,2 %). L’adhésion des répondants variait, mais 40,5 % utilisaient des parties des deux documents. La variabilité considérable de la pratique était observée lorsque les recommandations étaient contradictoires. Bien que son utilisation ne soit pas recommandée par l’un ou l’autre de ces organismes, la moitié des répondants (50,0 %) signalaient utiliser le score CHA2DS2-VASc comme outil d’évaluation du risque d’accident vasculaire cérébral. Conclusions: Bien que la plupart des MU interrogés connaissaient au moins un document sur la FA des organismes, plusieurs signalaient utiliser des parties des deux documents. Lorsque les recommandations étaient contradictoires, les MU étaient divisés sur la prise de décision. Ces résultats confirment la nécessité d’améliorer le consensus entre les organismes et d’améliorer davantage l’application des connaissances.